Front Cover: Functional Fermented Probiotics, Prebiotics, and Synbiotics from Non‐Dairy Products: A Perspective from Nutraceutical. Issue 14 (20th July 2022) - Kumar, Dharmendra; Lal, Milan Kumar; Dutt, Som; Raigond, Pinky; Changan, Sushil Sudhakar; Tiwari, Rahul Kumar; Chourasia, Kumar Nishant; Mangal, Vikas; Singh, Brajesh
Abstract : Mol. Nutr. Food Res . 2022, 66, 202101059 DOI: 10.1002/mnfr.202101059 The non‐dairy based probiotics play the role of synbiotics because they have prebiotics in the substrate matrix, which proliferates probiotic microorganisms by various mechanisms such as SCFAs, EPS and volatile compounds. Hence, non‐dairy based probiotics have synergetic effect on human health and gut biota which have beneficial effect on human health. This is reported by Dharmendra Kumar and co‐worker in the article number 2101059 .